A PHARMACOLOGICAL STUDY ON AYURVEDA MANAGEMENT ON HEALING PROCESS OF TIBIA OF RATS WITH SPECIAL REFERENCE TO ARJUNA KSHEERA PAKA - Suguna, *K.; Dixit, Renu; Bhaskar Reddy, K.V.Vijaya (International Journal of Ayurveda and Pharma Research, 2017)
The present study was under taken to evaluate the effect of Terminalia arjuna Linn on the healing process of experimentally fractured tibia of rats. 12 Adult male wistar rats were grouped into I, II and III groups. Arjuna, a Bhagna Sandhanakara drug, mentioned in Vrindamaddhava is taken for the study.The solution of test drugs for Group I is 2mg of Terminalia arjuna powder TAP boiled with milk and Group II by 8mg of Terminalia arjuna Ksheera paka powder TAKP (Arjuna powder boiled with milk and heated till it is semisolid and after cooling it is made into fine powder) and Group III with 2mg Placebo (PG) rice powder with milk. The test solution was introduced into the oral cavity of male wister rats by rat feeding needle.On observing the radiological images, Group I and Group II shows improvement in healing process of tibia by 30th day after treatment due to Jeevaniya and Sandhaniya karma of milk which causes synergetic action of Arjuna karmas than Group III. Group II shows early healing capacity of calcification than Group 1 by 20th day compared in between group I and Group III. Based on all the observed results it can be concluded that Group 2 (Terminalia arjuna ksheerapaka powder (TAKP) is highly significant in calcification between the three groups.